Sulfur reagents in organic synthesis - Metzner, Patrick (Best synthetic methods., 1994)
Designed for the practising organic chemist, this book details over a hundred experimental procedures using sulfer compounds in organic synthesis. Many of these methods are new to the literature, having been published since 1991, and illustrate the striking versatility of the use of sulfur reagents. Examples are simple to perform and extremely useful, and as such this book will be an invaluable aid to all involved in synthetic organic chemistry, whether in academic or industrial laboratories.